Secondary School Teachers ’ Utilization of Feedback in the Teaching and Learning of Mathematics in Tanzania - Lema, Godson; Maro, Wadrine (Papers in Education and Development, 2016)
This study presents the findings of a study conducted to explore secondary school mathematics teachers ' understanding and utilization of feedback in the teaching and learning of mathematics in Tanzania. The study was anchored on the premise that effective feedback is a prerequisite for the successful teaching and learning of Mathematics. Feedback given in line with formative assessment helps learners to be aware of any gaps that exist between their desired learning goal and their current knowledge, skills and understanding of the subject matter. The major concern of assessment practices in Tanzania is the fact that feedback as an aspect of formative assessment is not given enough attention in the teaching and learning of mathematics. The study employed a mixed-methods research approach and consisted of 36 respondents drawn from twelve private and public secondary schools in Arusha City and Kinondoni Municipality. The data were collected through interviews, classroom observation and documentary analysis. Quantitative data from classroom observation were analysed statistically using the Mann-Whitney U test and Kruskal-Wallis H test. Qualitative data from interviews were analysed using thematic analysis. The findings showed that mathematics teachers knew little about the utilisation of feedback in teaching and learning mathematics. In particular, the findings indicated that utilisation of feedback in the classroom was influenced by teachers ' demographic characteristics, such as gender, school type and teaching experience, while characteristics such as teachers ' qualifications, number of periods and class size had no influence on teachers ' provision of feedback. The findings further revealed that teachers ' lack of awareness of feedback influenced its effective utilisation in mathematics classes. This study recommends provision of in-service training focusing on formative assessment of mathematics teachers. Key words: Feedback, formative assessment, classroom assessment, teaching and learning mathematics.